The impact of planet wakes on the location and shape of the water ice line in a protoplanetary disk - Ziampras, Alexandros; Ataiee, Sareh; Dullemond, Cornelis (Astronomy and astrophysics, 2020)
Context. Planets in accretion disks can excite spiral shocks and if these planets are massive enough, they can even open gaps in their vicinity. Both of these effects can influence the overall thermal structure of the disk.Aims. We model planets of different masses and semimajor axes in disks of various viscosities and accretion rates to examine their impact on disk thermodynamics and to highlight the mutable, non-axisymmetric nature of ice lines in systems with massive planets.Methods. We conducted a parameter study using numerical hydrodynamics simulations where we treated viscous heating, thermal cooling, and stellar irradiation as additional source terms in the energy equation, with some runs including radiative diffusion. Our parameter space consists of a grid containing different combinations of planet and disk parameters.Results. Both gap opening and shock heating can displace the ice line, with the effects amplified for massive planets in optically thick disks. The gap region can split an initially hot (T > 170 K) disk into a hot inner disk and a hot ring just outside of the planet’s location, while shock heating can reshape the originally axisymmetric ice line into water-poor islands along spirals. We also find that radiative diffusion does not alter the picture significantly in this context.Conclusions. Shock heating and gap opening by a planet can effectively heat up optically thick disks and, in general, they can move or reshape the water ice line. This can affect the gap structure and migration torques. It can also produce azimuthal features that follow the trajectory of spiral arms, creating hot zones which lead to “islands” of vapor and ice around spirals that could affect the accretion or growth of icy aggregates.
Gesehen am 03.02.2020